2022
DOI: 10.3390/polym14050861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Functional Fillers on Tribological Characteristics of Acrylonitrile Butadiene Rubber after High-Pressure Hydrogen Exposures

Abstract: In a high-pressure hydrogen environment, the sealing rubber material is swelled by hydrogen, and the mechanical and tribological properties are reduced, causing various problems in the sealing performance. The focus of this study was the effect of the filler type and content on the tribological characteristics of rubber after exposure to high-pressure hydrogen. Acrylonitrile butadiene rubber specimens were exposed to high-pressure hydrogen at 96.6 MPa, and the change in the amount of wear with time after expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The holding pin for the weight is a cylindrical rod with a 4 mm stainless steel ball at its end. The integrated computer monitored the surface stress in relation to the force used to rotate the circular stage at a preset sliding distance (500 m) and revolution per minute (200 rpm) [ 26 ]. The coefficient of friction can therefore be determined by using Equation (1) [ 27 ]: Where μ is coefficient of friction.…”
Section: Characterizationsmentioning
confidence: 99%
“…The holding pin for the weight is a cylindrical rod with a 4 mm stainless steel ball at its end. The integrated computer monitored the surface stress in relation to the force used to rotate the circular stage at a preset sliding distance (500 m) and revolution per minute (200 rpm) [ 26 ]. The coefficient of friction can therefore be determined by using Equation (1) [ 27 ]: Where μ is coefficient of friction.…”
Section: Characterizationsmentioning
confidence: 99%
“…Choi et al studied the friction and wear behavior of NBR rubber under continuous sliding in air after high-pressure exposure in hydrogen [29]. They reported that the hydrogen-induced damage was related to the tribological properties of filled NBR.…”
Section: Introductionmentioning
confidence: 99%